Impact of critical success factors and supportive leadership on sustainable success of renewable energy projects: Empirical evidence from Pakistan. (March 2022) - Zaman, Shah; Wang, Zilong; Rasool, Samma Faiz; Zaman, Qamar uz; Raza, Hamid
Abstract: This study aims to investigate the relationship between critical success factors and sustainable project success of renewable energy projects of Pakistan. In this study, supportive leadership intervenes between critical success factors and sustainable project success. The study adopts a quantitative research approach using survey data from the project managers, project team leaders, and project staff of renewable energy projects. A questionnaire survey approach is used to collect data. For data analysis, we used the partial least square structural equation modeling through SmartPLS 3.2.2. The outcomes indicate that in the direct relationship, organizational, communication, and technical factors positively and significantly affect the sustainable project success, while team factors show insignificant relationships with sustainable project success. Moreover, organizational, team, and communication factors positively and significantly affect supportive leadership, while technical factors have established an insignificant relationship with supportive leadership. Besides, supportive leadership also positively and significantly impacts sustainable project success. The outcomes also show that supportive leadership positively and significantly mediates between organizational, team and communication factors and sustainable project success. Meanwhile, supportive leadership negatively and insignificantly mediates between technical factors and sustainable project success. The concluding remarks also discussed the practical implications, limitations, and future research directions. Highlights: Identify the critical success factors. Used the Partial least squares structural equation modelling. This study suggests strategies for renewable energy projects. Critical success factors improve the sustainable project success. Supportive leadership improve the sustainable project success.